THE PNUMA AND THE ENVIRONMENTAL EDUCATION IN PERU - Delgado Santa Gadea, Kenneth (2014)
The environment problems on all the world, there are threat contamination to present and future of new generations. An is the greenhouse gas emissions, because determine or produce the climate change; this problem us affect. The environmental education comprise an ensemble of several educative actions, principally since the no formal and informal education. This educative actions find to mitigate the climate change effects. The PNUMA is an opportunity for research and repotenciate the environmental education field.